Phosphorus availability in oxiddic solis treated whith lime and silicate applications - Sandim, Aline da Silva [UNESP]; Büll, Leonardo Theodoro [UNESP]; Furin, Ariane Reis [UNESP]; Lima, Géssica da Silva [UNESP]; Garcia, Jader Luis Nantes [UNESP] (FapUNIFESP (SciELO), 2014)
Based on the assumption that silicate application can raise soil P availability for crops, the aim of this research was to compare the effect of silicate application on soil P desorption with that of liming, in evaluations based on two extractors and plant growth. The experiment was carried out in randomized blocks with four replications, in a 3 × 3 × 5 factorial design, in which three soil types, three P rates, and four soil acidity correctives were evaluated in 180 experimental plots. Trials were performed in a greenhouse using corn plants in 20-dm3 pots. Three P rates (0, 50 and 150 mg dm-3) were applied in the form of powder triple superphosphate and the soil was incubated for 90 days. After this period, soil samples were collected for routine chemical analysis and P content determination by the extraction methods resin, Mehlich-1 and remaining P. Based on the results, acidity correctives were applied at rates calculated for base saturation increased to 70 %, with subsequent incubation for 60 more days, when P content was determined again. The acidity correctives consisted of: dolomitic lime, steelmaking slag, ladle furnace slag, and wollastonite. Therefore, our results showed that slags raised the soil P content more than lime, suggesting a positive correlation between P and Si in soil. Silicon did not affect the extractor choice since both Mehlich-1 and resin had the same behavior regarding extracted P when silicon was applied to the soil. For all evaluated plant parameters, there was significant interaction between P rates and correctives; highest values were obtained with silicate.

Partindo do princípio que a aplicação do silicato pode resultar em aumento na disponibilidade de P no solo para as culturas, objetivou-se estudar a influência da silicatagem, em comparação à calagem, na dessorção de P em solos, avaliada por dois extratores e pelo crescimento da planta. O delineamento experimental utilizado foi em blocos casualizados, com quatro repetições, em esquema fatorial 3 × 3 × 5, constituído por três solos, três doses de P e quatro corretivos de acidez, além de um tratamento sem correção da acidez, totalizando 180 parcelas experimentais. O experimento foi realizado em casa de vegetação, em vasos de 20 dm3 . Os solos foram submetidos a três doses de P (0, 50 e 150 mg dm-3), tendo como fonte superfosfato triplo em pó e mantidos incubados por 90 dias. Após o período de incubação, foram realizadas amostragens para análise química de rotina e determinações dos teores de P pelos métodos resina, Mehlich-1 e P remanescente. Com base nesses resultados, foi realizada a aplicação dos corretivos de acidez com as doses calculadas a fim de elevar a 70 % o valor de saturação por bases, permanecendo incubados por mais 60 dias; após, novas determinações dos teores de P foram realizadas. Os corretivos de acidez utilizados foram: calcário dolomítico, escória de aciaria, escória forno de panela e wollastonita. A cultura utilizada foi a do milho. Com os resultados, observou-se que as escórias aumentaram os teores de P no solo, quando comparadas ao calcário, sugerindo a interação positiva entre Si e P no solo. O uso do Si não interferiu na escolha do extrator, pois tanto o Mehlich-1 como a resina apresentaram o mesmo comportamento, quando houve a adição de Si ao solo em relação ao P extraído. Para todos os parâmetros analisados na planta, houve interação significativa entre as doses de P e os corretivos utilizados, com maiores valores com o uso de silicatos.
Disponibilidade de fósforo em razão da aplicação de calcário e silicatos em solos oxídicos
Keywords: Phosphorus adsorption; Silicate application; Liming; Silicon-phosphorus interaction; Adsorção de fósforo; Silicatagem; Calagem; Interação silício-fósforo